ANALISIS POTENSI DAN PELUANG SEBAGAI DESTINASI WISATA PENGAMATAN BURUNG ENDEMIK (BIDRWATCHING) - Ratri Paramita; AAI M Septiviari (Institut Pariwisata dan Bisnis Internasional, 2014)
Tourism Regions West Flores is not only a tourist attraction Komodo National Park (KNP) as a World Heritage Site which has become an international tourist attraction. However, West Flores also stores the value of diversity of fauna in the form of four species of birds that have the potential as a tourist endemic bird watching. From the tourist market trend in the past 10 years, tourists birdwatchers (Birdwatcher) are rising significantly. So that this phenomenon provides a significant opportunity for Indonesia as a State No. 1 in the world as a country which has the largest number of endemic birds in the world with 372 endemic bird species. This is very good potential to be developed in improving the welfare of society through the development of alternative tourism industry sector.Â